Metagenomics reveal the role of microorganism and GH genes contribute to Sichuan South-road dark tea quality formation during pile fermentation. (15th March 2023) - Zou, Yao; Yuan, Yue; Liu, Minqiang; Li, Xian; Lai, Yuqing; Liu, Xuyi; Tan, Liqiang; Tang, Qian; Chen, Wei; Li, Dan; Xu, Wei
Abstract: Microbes are critical for the flavor development of Sichuan South-road Dark Tea (SSDT) during pile-fermentation. However, their mechanism of action has not been fully elucidated yet. In this study, the SSDT microbial metagenome obtained from the different locations of piled tea center during the pile-fermentation metaphase were functionally annotated, and the glycoside hydrolase (GH) genes of the core functional strain were comprehensively analyzed. The results revealed that carbohydrate metabolism (8.2%) were predominant in the total SSDT microbial metagenome. GHs (39.8%) and glycosyl transferases (GTs, 37.3%) were abundant in the SSDT microbes. Moreover, Aspergillus niger was prevailing in SSDT, with 220  GH genes being distributed in 43 GH subfamilies and GH3, GH5, GH13, GH16, GH18, and GH28 being highly abundant. The expression patterns of the GH genes of Aspergillus niger M10 varied among different stages of submerged and solid-state fermentation. Notably, ANI_1_1714074 (xylosidase gene belongs to GH31) and ANI_1_2704024 (β-N-acetylglucosaminidase gene belongs to GH3) might be the potential functional genes degrading polysaccharides in Aspergillus niger M10. It was hypothesized that SSDT microbes, especially Aspergillus niger M10, have an abundant repertoire of carbohydrate-degrading enzymes, and may actively participate in tea taste formation through GHs during pile-fermentation. Highlights: Abundant glycoside hydrolases occurred in Sichuan South road dark tea microbes. ANI_1_1714074 and ANI_1_2704024 may be key functional genes degrading polysaccharide. AsPergillus niger M10 may involve in tea taste formation via GH genes expression.